Improving the Precision of Multiparameter Estimation in the Teleportation of Qutrit under Amplitude Damping Noise. Issue 3 (7th February 2023) - Li, Yan‐Ling; Zeng, Yi‐Bo; Yao, Lin; Xiao, Xing
Abstract: Since the initial discovery of quantum teleportation, it is devoted to transferring unknown quantum states from one party to another distant partner. However, in the scenarios of remote sensing, what people truly care about is the information carried by certain parameters. The problem of multiparameter estimation in the framework of qutrit teleportation under amplitude damping (AD) noise is studied. Particularly, two schemes are proposed to battle against AD noise and enhance the precision of multiparameter estimation by utilizing weak measurement (WM) and environment‐assisted measurement (EAM). For two‐phase parameters encoded in a qutrit state, the analytical formulas of the quantum Fisher information matrix can be obtained. The results prove that the scheme of EAM outperforms the WM one in the improvements of both independent and simultaneous estimation precision. Remarkably, the EAM scheme can completely ensure the estimation precision against the contamination by AD noise. The reason should be attributed to the fact that EAM is carried out after the AD noise. Thus, it extracts information from both the system and the environment. The findings show that the techniques of WM and EAM are helpful for remote quantum sensing and can be generalized to other qutrit‐based quantum information tasks under AD decoherence. Abstract : Two schemes are proposed to battle against amplitude damping (AD) noise in qutrit teleportation and enhance the precision of multiparameter estimation by utilizing weak measurement (WM) and environment‐assisted measurement (EAM). The results prove that the techniques of WM and EAM are helpful for remote quantum sensing and the efficiency of EAM scheme is significantly better than that of WM scheme.